Study of the Isomeric Ratio of 135m,g 54Xe in Photofission 23793Np in Giant Dipole Resonance Region - Thiep, Tran Duc; An, Truong Thi; Vinh, Nguyen The; Cuong, Phan Viet; Khai, Nguyen Tuan; Gangrski, Iu. P.; Penhionzkevich, Iu. E.; Zemenhik, V. I.; Mishinski, G. V. (Communications in Physics, 2008)
In this work we present the results of measurement of the isomeric ratio of fission fragment e in photofission of 237Np induced by bremsstrahlung in the Giant Dipole Resonance Region by the method using the inert gaseous flow. The experiments have been performed at the electron accelerator Microtron MT-25 of the Flerov laboratory of Nuclear Reaction, Joint Institute for Nuclear Research, Dubna, Russia. The results were discussed and compared with that of other authors.